Unlocking Uzbekistan's Growth Through Project Financing: Membuka Kunci Pertumbuhan Uzbekistan Melalui Pembiayaan Proyek - Akhatkulov , Akromjon (Indonesian Journal of Law and Economics Review, 2024)
This study examines the implementation and impact of project financing in Uzbekistan's unique economic landscape, particularly its role in fostering investments in fixed capital. Given the country's transition towards market reforms, the research aims to assess how project financing contributes to economic development amidst these changes. Utilizing a mixed-methods approach that combines quantitative data and qualitative interviews, preliminary results highlight the effective mobilization of substantial investments in key sectors such as energy and infrastructure. However, challenges in regulatory and financial transparency remain. The findings suggest that while project financing holds significant potential for economic growth in transitional economies like Uzbekistan, improvements in governance and financial regulations are crucial to optimize its benefits. Highlights: Economic Transition: Project financing boosts Uzbekistan's market reforms. Methodological Insight: Mixed-methods reveal financing impacts. Regulatory Challenges: Improved governance necessary for success. Keywords: Project Financing, Credit Portfolio, Economic Development, Fixed Capital Investment, Transitional Economiesm